Bis(trialkylsilyl) peroxides as alkylating agents in the copper-catalyzed selective mono-N-alkylation of primary amides. Issue 48 (1st June 2017) - Sakamoto, Ryu; Sakurai, Shunya; Maruoka, Keiji
Abstract : The copper-catalyzed selective mono- N -alkylation of primary amides with bis(trialkylsilyl) peroxides as alkylating agents was reported. Abstract : The copper-catalyzed selective mono- N -alkylation of primary amides with bis(trialkylsilyl) peroxides as alkylating agents was reported. The results of a mechanistic study suggest that this reaction should proceed via a free radical process that includes the generation of alkyl radicals from bis(trialkylsilyl) peroxides.